Haiti : Staff Report for the 2015 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that a drought that affected agricultural output slowed Haiti's GDP growth to 2.7 percent in FY2014, but inflation remained in the mid-single digits. The overall fiscal deficit of the central government remained high, in part owing to one-off investment related to Hurricane Sandy. International reserves remained appropriate at about 5 months of imports. The implementation of structural reforms to support growth underpins the medium-term outlook, which is nonetheless subject to downside risks. GDP growth in FY2015 is expected to be between 2-3 percent, and to increase to 3-4 percent in the medium term.